The Effects of Patient Positioning on the Outcome During Posterior Cranial Fossa and Pineal Region Surgery - Mavarez-Martinez, Ana; Israelyan, Lusine A.; Soghomonyan, Suren; Fiorda-Diaz, Juan; Sandhu, Gurneet; Shimansky, Vadim N.; Ammirati, Mario; Palettas, Marilly; Lubnin, Andrei Yu; Bergese, Sergio D. (Frontiers in Surgery, 2020)
Background: Surgery on posterior cranial fossa (PCF) and pineal region (PR) carries the risks of intraoperative trauma to the brainstem structures, blood loss, venous air embolism (VAE), cardiovascular instability, and other complications. Success in surgery, among other factors, depends on selecting the optimal patient position. Our objective was to find associations between patient positioning, incidence of intraoperative complications, neurological recovery, and the extent of surgery. Methods: This observational study was conducted in two medical centers: The Ohio State University Wexner Medical Center (USA) and The Burdenko Neurosurgical Institute (Russian Federation). Patients were distributed in 2 groups based on the surgical position: sitting position (SP) or horizontal position (HP). The inclusion criteria were adult patients with space-occupying or vascular lesions requiring an open PCF or PR surgery. Perioperative variables were recorded and summarized using descriptive statistics. The post-treatment survival, functional outcome, and patient satisfaction were assessed at 3 months. Results: A total of 109 patients were included in the study: 53 in SP and 56 in HP. A higher proportion of patients in the HP patients had greater than 300mL intraoperative blood loss compared to the SP group (32% versus 13%; p=0.0250). Intraoperative VAE was diagnosed 40% of SP patients compared to 0% in the HP group (p<0.0001). However, trans-esophageal echocardiographic (TEE) monitoring was more common in the SP group. Intraoperative hypotension was documented in 28% of SP patients compared to 9% in HP group (p=0.0126). A higher proportion of SP patients experienced a new neurological symptom compared to the HP group (49% versus 29%; p= 0.0281). The extent of tumor resection, postoperative 3-month survival, functional outcome, and patient satisfaction were not different in the groups. Conclusions: The SP was associated with, less intraoperative bleeding, increased intraoperative hypotension, VAE, and postoperative neurological deficit. More HP patients experienced macroglossia and increased blood loss. At 3 months, there was no difference of parameters between the two groups.